Community-Based Training and Coaching Programs to Adjust English Language Skills - Muhammad Aswad; Rafiqa (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2023)
English is one of the essential skills in the era of globalization. However, English language skills in MA DDI Banua Sendana students still need to improve, as evidenced by the results of preliminary observations made by servants or researchers. English learning outcomes at the school still need to meet the KKM or Minimum Completeness Criteria (KKM) standards. Therefore , this community service program was carried out through a community-based training and coaching program to improve English language skills in MA DDI Banua Sendana students. The method used in this program is community-based training and coaching for one month for the students and English teachers involved. The training and coaching focused on introducing vocabulary, grammar, and speaking and writing skills in English. In addition, the program also involved English language students as training and coaching facilitators. The program results showed a significant improvement in the English language skills of MA DDI Banua Sendana students. In a test conducted after the program ended, there was a 30% increase in the average score on speaking, writing, and understanding English vocabulary. In addition, the program also succeeded in increasing students' motivation and interest in learning English. This community service program concludes that community-based English language training and coaching can be a solution in improving English language skills in primary school students in rural areas. This program can continue to be developed and adopted by other educational institutions to provide more significant benefits to communities in rural areas.